2017
DOI: 10.1186/s40729-017-0066-6
|View full text |Cite
|
Sign up to set email alerts
|

Customized SmartPeg for measurement of resonance frequency of mini dental implants

Abstract: BackgroundOne-piece narrow diameter implants (NDIs) have been recommended as “Single-tooth replacements in the anterior zones, single posterior, multiple-unit fixed dental prosthesis (FDP), edentulous jaws to be rehabilitated with FDP, and edentulous jaws rehabilitation with overdentures in situations with reduced mesiodistal space or reduced ridge width.” (ITI consensus 2013). Since NDIs can be immediately loaded, it is important to be able to carry out stability testing. We developed and validated a customiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…During the follow-up visits, the periodontal status related to each implant was evaluated by measuring their pocket depth and analyzing their gingival and plaque indices. The obtained results were consistent with the previously obtained data by Romeo et al (10) and Dhaliwal et al (11) They found that there was no significant difference in primary stability between MDIs and conventional implants. According to the obtained results, the marginal bone loss in group I (conventional implant) was less than in group II (Mini implants) after threeand nine-months post-operation.…”
Section: Discussionsupporting
confidence: 92%
“…During the follow-up visits, the periodontal status related to each implant was evaluated by measuring their pocket depth and analyzing their gingival and plaque indices. The obtained results were consistent with the previously obtained data by Romeo et al (10) and Dhaliwal et al (11) They found that there was no significant difference in primary stability between MDIs and conventional implants. According to the obtained results, the marginal bone loss in group I (conventional implant) was less than in group II (Mini implants) after threeand nine-months post-operation.…”
Section: Discussionsupporting
confidence: 92%
“…Exact descriptions of the measurement procedure in the studies mentioned above are lacking. In an animal study, another SmartPeg prototype was developed for the same MI system used in the present study [42]. The MIs were inserted into the tibia/femur of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Exact descriptions of the measurement procedure in the studies mentioned above are lacking. In an animal study, another SmartPeg prototype was developed for the same MI system used in the present study [40]. The MIs were inserted into the tibia/femur of rabbits.…”
Section: Discussionmentioning
confidence: 99%